2012
DOI: 10.1039/c2lc21154h
|View full text |Cite
|
Sign up to set email alerts
|

Single line particle focusing induced by viscoelasticity of the suspending liquid: theory, experiments and simulations to design a micropipe flow-focuser

Abstract: We perform 3D numerical simulations, heuristic modeling and microfluidic experiments to demonstrate, for the first time, the presence of a bistability scenario for transversal migration of particles suspended in a viscoelastic liquid flowing in a pipe. Our results show that particle migration, either at the centerline or at the wall, can be controlled by the rheological properties of the suspending liquid and by the relative dimensions of the particle and tube. Proper selection of these parameters can promote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
224
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(247 citation statements)
references
References 23 publications
15
224
2
1
Order By: Relevance
“…Under the assumption of zero Reynolds number and small blockage ratio, Ho & Leal (1976) showed that a lateral force, originating from the normal stress differences, drives the particle towards the lower-shear region in a second-order fluid. This conclusion has been verified in other experiments and simulations, where particles move to the central axis of a circular tube (Tehrani 1996;D'Avino et al 2012;Romeo et al 2013;Kang et al 2014) and to both centreline and corners in a rectangular channel (Yang et al 2011;Leshansky et al 2007). Based on simulations of the Giesekus and Phan Thien-Tanner constitutive equations, Villone et al (2011, 2013) and D'Avino et al (2012 observed bistable dynamics of particles in shear-thinning fluids, i.e.…”
Section: Introductionsupporting
confidence: 51%
“…Under the assumption of zero Reynolds number and small blockage ratio, Ho & Leal (1976) showed that a lateral force, originating from the normal stress differences, drives the particle towards the lower-shear region in a second-order fluid. This conclusion has been verified in other experiments and simulations, where particles move to the central axis of a circular tube (Tehrani 1996;D'Avino et al 2012;Romeo et al 2013;Kang et al 2014) and to both centreline and corners in a rectangular channel (Yang et al 2011;Leshansky et al 2007). Based on simulations of the Giesekus and Phan Thien-Tanner constitutive equations, Villone et al (2011, 2013) and D'Avino et al (2012 observed bistable dynamics of particles in shear-thinning fluids, i.e.…”
Section: Introductionsupporting
confidence: 51%
“…The correlation between the particle defocusing and shear thinning is consistent with existing experimental and numerical observations showing that the shear thinning effect always drive the particle closer to the wall in viscoelastic fluids. 47,[52][53][54] Fluids with high viscosities are also undesirable for particle manipulation, since throughput is limited by high pressure drop and multiple focusing pattern will exist over a wide range of flow rates due to low Re. In the 5 wt % PVP solution with high viscosity of 2.8×10 -2 Pa.s, particles appeared at the channel corners even at 1.5 ml/h due to the low Re (Re = 0.3).…”
Section: Resultsmentioning
confidence: 99%
“…Even in the case of synthetic polymers, the elasticity number El (Wi/Re l relax m/2rR 2 ) can be further enhanced if polymers are dissolved into highly viscous media. However, high pressure is required to drive high flow rates when such viscous media are used as working fluids 20 , which is an obvious drawback for portable microfluidic applications. Our present study demonstrates that in dilute DNA solutions it is possible to achieve significantly high El value at low viscosities (B2 cP), which allows high flow rates at low pumping pressures.…”
Section: Resultsmentioning
confidence: 99%
“…The lateral particle migration under macroscopic flows has long been recognized 16 . Additionally, two-dimensional (2D) (midplane) particle focusing in a slit microchannel 18 and 3D focusing in a square microchannel 19 or a microtube 20 have recently been reported. The shear viscosity of a dilute l-DNA solution (0.0005 (w/v)% in the present work) is nearly constant irrespective of shear rate (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation